Complicity in sociology and community‐based participatory research with Marshallese. (25th February 2022) - McElfish, Pearl A.; Purvis, Rachel S.; Riklon, Sheldon; Willis, Don E.
Abstract: Complicity with colonialism can be reflected in a particular approach to research, whose interests it serves, and who has power or ownership over the research process. It can also be reflected in neglect, inaction or methodological erasure of groups historically subjected to domination by colonial empires. Social scientists have often failed to account for colonialism's role or the complicit role they have played. We provide a brief historical overview of colonialism in the Marshall Islands and the role social scientists—and their methodological and epistemological approaches—played in the US empire's expansion into the region. We discuss the tenets of Community Based Participatory Research (CBPR), setting the research agenda, co‐direction of the research process, research team membership, collaboration challenges, and the action and outputs which have come from our team's health disparities research among the largest Marshallese population in the continental US. We argue CBPR is a promising but imperfect approach to guarding against complicity within medical sociology and situate our methodological approach within ongoing debates regarding objectivity and advocacy within sociology. We reflect on successes and shortcomings of our CBPR efforts to address health disparities among Marshallese, as well as how those successes and shortcomings overlap with questions of complicity.